COMPARISON OF 0.75% HYPERBARIC ROPIVACAINE WITH FENTANYL AND 0.75% HYPERBARIC ROPIVACAINE WITH DEXMEDETOMIDINE FOR SPINAL ANAESTHESIA IN ELECTIVE LOWER LIMB SURGERIES - KAUR, SIMRIT; SOUMITH, KETHAVATH; KUNDRA, TANVEER SINGH; GREWAL, TEJINDERPAL KAUR; SHAMNAD, MOHAMMED; BINDRA, TRIPAT KAUR (International Journal of Current Pharmaceutical Research, 2026)
Objective: Spinal anaesthesia is a preferred technique for lower limb surgeries due to its reliability and safety. Adjuvants like fentanyl and dexmedetomidine are commonly added to local anaesthetics to enhance block characteristics. To compare the sensory and motor block characteristics, haemodynamic profile, sedation, duration of analgesia, and complications of intrathecal 0.75% hyperbaric ropivacaine with fentanyl versus dexmedetomidine in elective lower limb surgeries. Methods: After institutional ethics committee approval, 60 ASA I–II patients aged 18–60 y scheduled for elective lower limb surgeries were randomised into two groups (n=30 each). Group I received 2 ml of 0.75% hyperbaric ropivacaine+25 µg fentanyl, and Group ii received 2 ml of 0.75% hyperbaric ropivacaine+10 µg dexmedetomidine intrathecally. Onset and duration of sensory and motor block, haemodynamics, sedation (Ramsay score), postoperative pain (VAS), and side effects were recorded. Data were analysed using Student’s t-test and chi-square test; p<0.05 was considered significant. Results: Onset of sensory (Group I: 2.76±0.08 min vs Group ii: 2.72±0.08 min; p=0.134) and motor block (Group i: 1.58±0.40 min vs Group ii: 1.38±0.37 min; p=0.053) was comparable. Duration of sensory block (Group I: 275.10±16.46 min vs Group ii: 310.13±14.94 min; p<0.001), motor block (Group I: 113.77±13.01 min vs Group ii: 124.30±6.91 min; p<0.001), and analgesia (Group I: 226.40±18.09 min vs Group ii: 280.60±13.90 min; p<0.001) was significantly longer in Group ii. Haemodynamic parameters and sedation scores remained stable and comparable. Incidence of side effects was similar. Conclusion: Intrathecal dexmedetomidine as an adjuvant to 0.75% hyperbaric ropivacaine provides significantly longer sensory and motor blockade and postoperative analgesia compared to fentanyl, with similar haemodynamic stability and side-effect profile.